A study on space efficiency in contemporary supertall mixed-use buildings. (15th June 2023) - Ilgın, Hüseyin Emre
Abstract: To date, no study provides an understanding of space efficiency in supertall (≥300 m) mixed-use buildings, taking into account key architectural and structural planning considerations. In this article, this critical issue was examined. Case study data were collected from 64 contemporary supertall towers to create more viable supertall mixed-use building projects. The results highlighted the following: (i) only the central core typology was used in the core arrangement; (ii) tapered and free forms were the most commonly employed; (iii) outriggered frame system was utilized predominantly; (iv) composite was the most preferred building material; (v) space efficiency varied inversely with the height of the building; and (vi) there was no significant difference between the effects of different structural systems on space efficiency, and similar findings were obtained for building forms. It is thought that this paper will guide key professionals such as architects, structural designers, and contractors in the planning of mixed-use towers. Highlights: Only the central core typology was used in the core arrangement. Tapered and free forms were the most commonly employed. Outriggered frame system and composite were utilized predominantly.. Space efficiency varied inversely with the height of the building. There was no significant difference between the effects of different structural systems and forms on space efficiency.